Adaptive Frame Skipping with Screen Dynamics for Mobile Screen Sharing Applications - Lim, Keun Woo; Ha, Jisu; Bae, Puleum; Ko, Jeonggil; Ko, Young Bae (IEEE Systems Journal, 2018)
The improvement in hardware capabilities of mobile devices has led to the active use of processor-heavy contents, such as multimedia files, on resource-limited platforms. In addition to simply enjoying such contents on mobile devices, recently commercialized protocols allow the real-time sharing of multimedia (or a mobile device's screen contents) with neighboring devices via wireless connection. However, unlike PC-scale computing platforms, use-case expansions on mobile devices face an additional technical challenge. Specifically, while the improved computation power is capable of handling processor-hungry applications, battery limitations hold back their full utilization. This paper acknowledges the fact that screen sharing on mobile devices can be attractive, but empirically show that minimizing the energy consumption is crutial, and introduces enhancements to the widely used H.264 encoder on mobile devices. Specifically, our enhancements target to minimize the transmission size of multimedia contents by analyzing the screen's dynamics. For contents with high dynamics, our scheme tries to maintain the video quality, while aggressively skipping frames for regions with minimal motion intensity. Our empirical evaluations show that the proposed light-weight enhancements reduce the size of a typical multimedia file by ∼42%, while maintaining a high user-perceived quality (e.g., Structural SIMilarity measure) of 0.925. Wirelessly sharing this video results in ∼31% lower frame transmission rate and up to ∼21% power savings in less dynamic regions.
Keywords: Adaptive frame skipping; Computing platform; Empirical evaluations; Frame transmission; Multimedia contents; Structural similarity; Technical challenges; Wireless connection; Adaptive frame rate control; codecs; communications technology; Miracast; mobile video compression; video codecs